ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP BERDASARKAN LANGKAH PENYELESAIAN POLYA - Luluk Lutfiya; Hari Sumardi; Teddy Alfra Siagian (LINEAR: Journal of Mathematics Education, 2021)
Mathematical Problem Solving Skill is one of the most important mathematical competencies for students to master. The problem solving used in this research is the complete step based on Polya. This type of research is descriptive research with a qualitative approach. The purpose of this study was to determine the distribution of the level of mathematical problem solving ability of SMPN 29 Bengkulu Utara students based on Polya's solving steps. The methods of data collections used form of text of problem solving skill, interviews, and documentations. The results of this study showed that the average overall mathematical problem solving ability of students at SMPN 29 Bengkulu Utara was 47.59% with sufficient criteria. The average student ability to understand the problem is 57.67% with sufficient criteria, the average problem planning ability is 56.08% of sufficient criteria, the average problem solving ability is 43.92% with sufficient criteria, and the average ability to re-examine or conclude is 32.67% with low criteria.